(untitled) (Research, Society and Development, 2022)
Himatanthus drasticus is a plant widely used for the treatment of various diseases such as ulcer, cancer, scarring, worms, inflammation in general, among other diseases. Due to its wide use, this species is widely used in biological and pharmacological assays. Thus, this work aims to carry out a literature review of the aforementioned species, highlighting its ethnopharmacology, phytochemistry, and biological activities. The keyword “Himatanthus drasticus” and its synonyms “Plumeria drastica”, “Himatanthus fallax” and “Plumeria fallax” were used through the Boolean operator “OR” as main indexes for searching in the following platforms PubMed, PubMed Central, SciElo, Scopus and Web of Science. Articles published in English and Portuguese in the last 15 years (2006-2021) were considered. Studies demonstrate that H. drasticus has studies that show a variety of relevant pharmacological activities. Among the most studied organs of H. drastiscus, the leaves stand out, which have several chemical constituents present, such as phenolic compounds, among them quercetin, quercetin 3-latyroside, isoquercetrin, rutin, among others. The biotechnological potential of H. drasticus is remarkable, with latex being the main product, thus corroborating the traditional therapy. Phytochemically, this species presents iridoids, belonging to the terpene class. Which may be responsible for the biological and pharmacological activities observed in this review. Studies about the conservation of this species are necessary, since it suffers anthropic pressure through its extractivism.